Against Scientism in Psychological Counselling and Therapy - Martin, Jack (Canadian Journal of Counselling and Psychotherapy, 2007)
Without intending to disparage appropriate social scientific inquiry into psychotherapy, the author argues that much psychotherapy literature and practice is scientistic, in that it overvalues ways of knowing associated with science alone. Two reasons in support of this claim are discussed. One reason, concerning the difficulty of establishing causal claims in psychotherapy, points to unresolved difficulties in acquiring scientific knowledge of psychotherapeutic effects and mechanisms of change. The other, concerning the moral constitution of much psychotherapeutic conversation and context, questions the appropriateness of scientific explanation as a sole basis for understanding the phenomena of psychotherapy. The main implication of the distinction that is drawn between science and scientism is that counsellor educators, counseling practitioners, and psychotherapy researchers might do well to adopt a more genuinely scientific attitude of criticalness and humility in the face of issues such as those discussed. Such criticalness also might be extended to embrace other ways of knowing, including some of those extant in certain areas of the arts and humanities, to complement currently available social scientific epistemic practices.